Metalinguistic knowledge about the native language and language transfer in gender assignment - Vanhove, Jan (Studies in Second Language Learning and Teaching, 2019)
Whereas Standard Dutch only distinguishes between two adnominal grammatical genders, substandard varieties of Belgian Dutch distinguish between three such genders. German, too, distinguishes between three genders. Nevertheless, when assigning gender to German nouns with Dutch cognates, speakers of Belgian Dutch are strongly influenced by Standard Dutch gender but to a much lesser degree (if at all) by substandard gender. On the hypothesis that a lack of metalinguistic knowledge about L1 substandard gender decreases its use as a source for transfer, I experimentally manipulated the metalinguistic knowledge about L1 substandard gender of 45 speakers of substandard Belgian Dutch varieties. I then assessed how strongly this manipulation affected the participants’ reliance on substandard gender distinctions when they assigned gender to L2 German nouns with Dutch cognates. Results confirm the strong influence of Standard Dutch, hint at a weak influence of substandard Dutch, and show no appreciable effect of the experimental manipulation.